A theoretical overview on effects of road humps on traffic speed, noise and volume in improving residential living environment - Bachok, Khairun Sarah Radhiah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin; Ibrahim, Mansor (2015)
This paper is part of an ongoing study that aims to analyse the effectiveness of road humps as a traffic calming measure in improving the living environment. It contains a review of how different road hump installations affect traffic speed, noise and volume. The findings are that differences in hump height and spacing are factors in influencing the speed selection by drivers. There are also uncertainties in regards to the effects of road humps on traffic noise levels, while road humps are effective in reducing the traffic volume only if more attractive alternative routes are available. Gaps identified in the previous studies are the consideration of road geometrics sample sizes, seasonal periods and development changes in before-and-after studies. Further studies should be conducted on the effects of road humps on traffic speed, noise and volume in consideration of the gaps identified from previous studies.